Concentration and competition in Ethiopian banking industry (a panel data analysis) - GEBEYEHU, Hailemariam Nega (KDI School, 2018)
The paper aims to investigate the degree of concentration and competition (market contestability) in the Ethiopian commercial banking industry using the Panzar-Rosse (P-R) Model. It also aims to empirically test for misspecification of the P-R model. The impact of different control variables on income types and thereby on competition is also examined. Finally, the paper attempts to formulate a testable hypothesis whether different income types are substitutes or compliments. All commercial banks operating in Ethiopia are considered for the analysis. Panel Random Effect Bootstrap Estimation is employed using quarterly data from 2002/03 (QIII) to 2014/15 (QIV). A total of 16 econometric panel models are estimated. In calculating prices of labor, physical capital and funds the most widely recommended proxies are used in the course of estimation. The results indicated that though the industry was highly contestable in early periods of the analysis, it still remains highly concentrated. The competition appears to be higher among private banks, though it endogenously comes from the existence of Commercial Bank of Ethiopia. Following Bikker et al (2006), we tested for misspecification of the empirical P-R Model and proved that the use of dependent variables scaled by asset sizes is biased towards competitive market conditions. Credit ceilings are found to have negative and significant influence on income statements of banks and then on competition. We could not find significant evidence about the impact of NBE bills on income and competition. Finally, we have formulated a testable hypothesis in identifying whether the relationship between income components is a substitute or compliment type. As far as the information we have, this is the first formulation in the analysis of income statement of banks from microeconomic theory perspective. Our results indicated that interest and non-interest components of income are non- compliments in the Ethiopian commercial banking industry. Based on our findings we would like to forward recommendations to policy makers and researchers. For policy makers, as our findings showed a non-favorable outcome of credit ceilings on income and competition, we recommend as much as possible such policies must be taken as last option and for a very short period. For researchers, we recommend the use of unscaled dependent variables in identifying market structure of the banking industry. Moreover, we would like to encourage researchers to test our newly formulated hypothesis in the banking industry so that we can get feedback.
Thesis(Master) --KDI School:Master of Development Policy,2018